2017
DOI: 10.1021/acs.iecr.7b00327
|View full text |Cite
|
Sign up to set email alerts
|

Application of Algae as Cosubstrate To Enhance the Processability of Willow Wood for Continuous Hydrothermal Liquefaction

Abstract: This work proposes a novel strategy to improve the continuous processing of wood slurries in hydrothermal liquefaction systems by co-processing with algae. Of all algae tested, brown seaweeds and microalgae perform best in preventing slurries dewatering, the main reason for pumpability issues with wood slurries. Rheological tests (viscosity-shear rate profile) indicate that the addition of these two algae to the wood slurry causes the highest increase in viscosity, which coincides with improved wood slurries s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 49 publications
0
20
1
Order By: Relevance
“…Over 30% of the biocrude, mainly consisting of fuel oil, was evaporated between 360 and 550 °C . This is higher than the value found in one study which used the mixture of microalgae and willow chips as feedstocks [35], indicating more heavy oil compounds was produced.…”
Section: Effect Of Temperature On Properties Of Biocrude Oilcontrasting
confidence: 69%
See 1 more Smart Citation
“…Over 30% of the biocrude, mainly consisting of fuel oil, was evaporated between 360 and 550 °C . This is higher than the value found in one study which used the mixture of microalgae and willow chips as feedstocks [35], indicating more heavy oil compounds was produced.…”
Section: Effect Of Temperature On Properties Of Biocrude Oilcontrasting
confidence: 69%
“…Until 550 °C, 81.5% (wt) of biocrude oil was volatilised. The remaining nonvolatile fraction was mainly coke and ash [35]. Nearly 40% of the biocrude oil evaporated between 180 and 360 °C.…”
Section: Effect Of Temperature On Properties Of Biocrude Oilmentioning
confidence: 99%
“…Therefore, sometimes studies are conducted with highly diluted feedstock, even with concentrations as low as 1%, as a work-around to pumpability issues. In general, pumpability of biomass slurries has not received much attention, but recently studies [28,79,103,104] have identified methodologies and tests to identify potentially pumpable slurries from different types of biomass including lignocellulosics, microalgae, and seaweed. A simple test dubbed the "syringe test", in which a biomass slurry is pressed through a standard medical syringe has been shown to be a fast and reliable method to determine whether a slurry is not pumpable [103]: if the slurry destabilizes and separates into a dry and a wet fraction, this particular slurry is most likely not pumpable.…”
Section: The Influence Of Dry Matter Concentrationmentioning
confidence: 99%
“…11,12 Recently, coliquefaction with macroalgae and microalgae has been suggested, which additionally can compensate for cost, seasonal variability, and availability of the feedstocks while microalgae also produce minimum char. 13,14 The majority of HTL studies are performed without catalyst while many use alkali salts, as in this study, to decrease char formation. Char is defined as the primary decomposition and secondary polymerization of thermally decomposed biomass whereas coke is due to catalytic polymerization inside catalyst pores.…”
Section: Introductionmentioning
confidence: 99%